Comparison of Dexmedetomidine and Fentanyl as Intrathecal Adjuvants to 0.5% Hyperbaric Bupivacaine for Lower Abdominal Surgery Under Subarachnoid Block - Deepa Allolli; G S Mahishale; B Rajendrakumar; Nazeer Ahmed K (Academia Anesthesiologica International, 2020)
Background: Adjuvants to spinal anesthesia can improve anesthesia and reduce pain intra- as well postoperatively. The present study compared the efficacy of dexmedetomidine and fentanyl added to intrathecal bupivacaine in lower abdominal surgeries. Subjects and Methods: Patients, aged 20 to 60 years in American Society of Anesthesiologists Grade 1 and 2, scheduled to undergo lower abdominal surgeries randomly received either 0.5 ml of 5 mcg Dexmedetomidine with 2.5 ml (12.5 mg) of Bupivacaine 0.5% heavy (Group D) or 0.5 ml of 25 mcg Fentanyl with 2.5 ml (12.5 mg) of Bupivacaine 0.5% heavy (Group F). Various intra-operative parameters were noted. Results: Highest sensory level achieved was significantly higher for Group F as compared to that for Group D (level 8 vs level 6; p-value <0.001). Time for two-segment regression, time of sensory regression to S1, regression to Bromage 0 and time to rescue analgesia was significantly higher for Group D as compared to Group F. Time for highest sensory level and the onset of Bromage 3 were not significantly different between the two study groups. Among the hemodynamic parameters, only heart rate was found to be significantly higher in Group F 20 minutes onwards during the procedure. Other than this none of the hemodynamic parameters was significantly different between the two study groups. Also, the proportion of patients with adverse effects were similarly distributed between the two study groups. Conclusions : Our results indicate that Dexmedetomidine may be used as an alternative to fentanyl for intrathecal adjuvant with hyperbaric bupivacaine.